Clinical Outcome of Extended Curettage with Postoperative Denosumab Administration for the Treatment of Campanacci Grade III Giant Cell Tumors of the Extremities - Zhang S; Zhao J; Song L (Cancer Management and Research)
Shuai Zhang,* JiaQi Zhao,* Lei Song Orthopedics Department, Southwest Hospital, The Army Military Medical University (The Third Military Medical University), Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shuai Zhang, Orthopedics Department, Southwest Hospital, The Army Military Medical University (The Third Military Medical University), No. 30 Gaotanyan Street, Shapingba District, Chongqing, 400038, People’s Republic of China, Email zhangshuai20030@163.comPurpose: To investigate the local recurrence rate, joint preservation status, and functional outcomes after extended curettage and postoperative denosumab treatment for Campanacci Grade III giant cell tumors of the extremities.Methods: We retrospectively reviewed 23 patients with Campanacci Grade III GCTB of the extremities in our hospital between January 2017 and June 2023 who underwent extended curettage and postoperative denosumab administration alone, without preoperative denosumab treatment. Patients were followed-up for adverse events of denosumab, surgical outcomes, limb function of lesions, and local recurrence following extended curettage with postoperative denosumab.Results: All incisions healed without deep infections or internal fixation failure. The mean age of the patients at surgery was 36.6 years, and the mean follow-up was 35.8 months (range, 6– 72 months). There of the 3 patients experienced a postoperative local recurrence. The recurrence rate was found to be 13.0%. Two patients were treated with repeat intralesional surgery with no additional recurrence two years later, and the other was treated with en bloc resection and reconstruction with a vascularized fibular graft. One patient experienced knee osteoarthritis without oral analgesics. No patient developed pulmonary metastases or malignant transformation of the GCTB. The mean Musculoskeletal Tumor Society functional score at the last follow up was 27.3 30 (range, 25– 29). No serious adverse events were observed after the denosumab treatment.Conclusion: Our observations suggest that extended curettage with postoperative denosumab administration is a reasonable option for treating Campanacci Grade III giant cell tumors of the extremities. Extended curettage with adjuvant denosumab therapy results in beneficial surgical downstaging, including a less morbid surgical procedure or delayed en bloc resection. Resection should be considered when the structural integrity cannot be regained after bone grafting or bone cement filling combined with internal fixation.Keywords: giant cell tumor of bone, curettage, denosumab, outcome